Bioactive Effect of Cinnamomum zealynicum bark Extracts on Some Locally Isolated Pathogenic Bacteria - A. Alsalim , Hutaf A.; S. Shawkat, Muayad; Al khwaildy, Majed Ibrahem (Iraqi Journal of Science, 2023)
A series of experiments were conducted to evaluate the antibacterial effect of Cinnamomum zealynicum bark aqueous , methanol, and chloroform extracts against some gram positive and gram negative pathogenic bacteria which isolated from wound, throat infection, urine and stool during the period from December /2013 to February /2014 from Alkarama hospital in Wasit. All these isolates were identified by using VITEK2 compact system. Antibiotic sensitivity test of the bacterial isolates was determined for ten antibiotics. Chemical analysis showed that Cinnamomum zeylanicum bark extracts contained different active compounds (phenoles, alkaloids, tannins, glycosides, coumarins, saponins, resins flavones and essential oil). The laboratory tests of antibacterial activity , showed that Staphylococcus aureus was the most affected by the extracts under study then followed with Enterococcus faecalis, Streptococcus pneumoniae, Escherichia coli and Klebsiella pneumoniae respectively. Aqueous extract showed highest values in MIC (400 μg/ml) and MBC (450 μg/ml) for S aureus, followed by chloroform (350 μg/ml, MIC and 400 μg/ml, MBC), then methanol (335 μg/ml, MIC and 375 μg/ml MBC) while the lowest values were recorded for K. pneumonia (MIC 175, 200 and 250 μg/ml, and MBC 200, 250 and 300 μg/ml respectively). In other hand inhibition zones appeared at 200 μg/ml for S. aureus and E. faecalis, and at 300 μg/ml for E. coli and S. pneumonia, and at 400 μg/ml for K. pneumoniae for aqueous extract, while methanol extract inhibition zones started from 100 μg/ml for S. aureus, and at 200 μg/ml for S. pneumonia and E. faecalis, and at 300 μg/ml for K. pneumonia and E. coli. Chloroform extract showed inhibition zones for S. pneumonia, E. faecalis and S. aureus at 200 μg/ml and for E coli and K. pneumoniae at 300 μg/ml.